(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The relationship of sociology with medical knowledge from the beginning was not an easy task between two different scientific fields to produce knowledge of disease, health and health care. Rather, sociological intervention in the field of medicine was not acceptable by specialists in the medical field. However, with the development of social life and overlapping multiple factors in the emergence of diseases, their diagnosis and methods of treatment, the gradual opening of medicine to sociology appeared in an attempt to introduce some social factors in the interpretation of diseases, the role of the patient, the relationship between the doctor and the patient, and the formulation of some scientific approaches and theories.